Risk of upper gastrointestinal bleeding in a cohort of new users of low-dose ASA for secondary prevention of cardiovascular outcomes - Lucía Cea Soriano; Luis A García Rodríguez (Frontiers Media S.A., 2010)
The Health Improvement Network UK primary care database was used to identify a cohort of 38 077 individuals aged 50-84 years with a first prescription of low-dose acetylsalicylic acid (ASA; 75-300 mg/day) for secondary prevention of cardiovascular or cerebrovascular events during 2000-2007. From this cohort, 169 incident cases of upper gastrointestinal bleeding (UGIB) were identified. Controls with no UGIB (n = 2000) were frequency-matched to the cases by age, sex and follow-up time. A nested case-control analysis was performed to determine risk factors associated with UGIB. The incidence of UGIB was 1.1 per 1000 person-years (95% CI, 1.0-1.3). Low-dose ASA users with a history of peptic ulcer disease had an increased risk of UGIB compared with those without (rate ratio [RR], 4.59; 95% CI, 2.87-7.33). Concomitant use of ASA and clopidogrel (RR, 1.61; 95% CI, 0.85-3.05) or non-steroidal anti-inflammatory drugs (NSAIDs; RR, 2.92; 95% CI, 1.77-4.82) conferred an increased risk of UGIB compared with ASA monotherapy. Discontinuation of ASA therapy (RR: 0.71, 95% CI, 0.42-1.20) and PPI co-treatment given since the start of ASA therapy (RR, 0.56; 95% CI, 0.33-0.96) were associated with a reduced risk of UGIB. In conclusion, in a cohort of individuals receiving low-dose ASA for secondary prevention of cardiovascular or cerebrovascular events, patients with a history of peptic ulcer disease, or who were receiving clopidogrel or NSAIDs had an increased risk of UGIB. The prescription of PPI therapy at the initiation of low-dose ASA reduced the risk of UGIB by almost half.